The cost of air pollution in Africa - Roy, Rana (OECD Development Centre Working Papers, 2016)
This paper is a first attempt at calculating the cost of air pollution in Africa. More precisely, it is a calculation of the major part of this cost: namely, the cost of premature deaths attributable to air pollution. It draws on the epidemiological evidence base assembled in the Global Burden of Disease Study 2013, in order to detail results for the health impacts of air pollution - in absolute terms and relative to selected other major risk factors, per country and for Africa as a whole. And it draws on the economic analyses developed by the present author, among others, in recent OECD work on the value of statistical life, in order to establish results for the economic cost of the health impacts of air pollution. In the period from 1990 to the present, and at each succeeding five-year interval in between, the death toll from air pollution in Africa has risen in tandem with the uninterrupted growth in the size of the urban population of Africa over this period. The total of annual deaths from ambient particulate matter pollution across the African continent increased by 36% from 1990 to 2013, from a then relatively low base of ≈ 180 000 in 1990 to ≈ 250 000 in 2013. Over this period, deaths from household air pollution also continued to increase, by 18%, from an already high base of ≈ 400 000 in 1990 to well over 450 000 in 2013. For Africa as a whole, as at 2013, the estimated economic cost of premature deaths from ambient particulate matter pollution was ≈ USD 215 billion. The estimated economic cost of premature deaths from household air pollution was ≈ USD 232 billion